(untitled) (Práxis Educativa, 2025)
This article seeks to understand meritocracy within the context of neoliberal logic and the challenges it poses to a liberating education. To this end, it adopts a reflective method with a dialectical-hermeneutic approach, articulating critical interpretive mediations based on the works of Brazilian sociologist Jessé Souza and American philosopher Michael Sandel, in dialogue with authors from a liberating perspective. The conclusions highlight: meritocracy is based on the internalization of colonialities and also on traditional education; as an ideology, it tends to justify inequalities and injustices in the form of privilege and success, as well as to educate for individualism and arrogance; as a tyranny, merit dismantles the universalization of public policies – including education – challenging liberating education to overcome this logic in the pursuit of good living and more solidaristic ways of living. Keywords: Traditional education. Coloniality. Ideology of merit.